1998
DOI: 10.1021/op970115w
|View full text |Cite
|
Sign up to set email alerts
|

A Calorimetric Investigation To Safely Scale-Up a Curtius Rearrangement of Acryloyl Azide

Abstract: N-Vinyl-O-benzyl urethane was prepared for use as a starting material in a multistep synthesis of a drug candidate. After unsuccessful attempts to employ non-Curtius options to prepare this intermediate, we decided to assess the thermodynamic and kinetic parameters of the acyl azide Curtius rearrangement and trapping of the intermediate isocyanate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 6 publications
1
38
0
Order By: Relevance
“…18,19 The structures of the products were established using IR, 1 H-NMR, 13 C-NMR and high resolution mass spectroscopy. Pilot thermolysis of the carbonyl azides 1-3 and 5 (1 mmol) at 220 °C for 15 minutes in anhydrous hexadecane (1 dm -3 ) led to the corresponding isocyanates 1a-3a and 5a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 The structures of the products were established using IR, 1 H-NMR, 13 C-NMR and high resolution mass spectroscopy. Pilot thermolysis of the carbonyl azides 1-3 and 5 (1 mmol) at 220 °C for 15 minutes in anhydrous hexadecane (1 dm -3 ) led to the corresponding isocyanates 1a-3a and 5a.…”
Section: Resultsmentioning
confidence: 99%
“…This technique is known to provide information which is valuable for the planning of thermochemical reactions that involve organic azides 12 or acryloyl azides. 13 This work was undertaken with a view to uncovering new evidence supporting the direct applicability of the CR to the synthesis of amines from carboxylic acids. Our long-standing interest in nitrogen pseudo-halogens such as azides and isocyanates arises from their utility in the synthesis of nitrogen-linked heteroaryls.…”
mentioning
confidence: 99%
“…The Curtius rearrangement converts acyl azides into isocyanates [100,109]. This has been used in flow chemistry [110], for example, for the preparation of PARP-1 inhibitors [111].…”
Section: Organic Reactions Of Azidesmentioning
confidence: 99%
“…Unfortunately, this rearrangement has the drawback that low molar mass acyl azides present an explosion hazard. 7 This safety issue has limited the industrial use of this transformation until recently, when Am Ende et al 8 reported a new experimental protocol, which enabled the use of this reaction under safer conditions even when conducted on a large scale. This and other protocols have revived interest in this rearrangement, particularly for industrial purposes.…”
Section: Introductionmentioning
confidence: 99%